The Teaching Perspectives Inventory (TPI) - Daniel D. Pratt; John B. Collins (Adult Education Research Conference, 2000)
The teaching of adults is a complex, pluralistic, and multi-faceted enterprise, but there have been no published studies that beyond identification and description of perspectives toward measurement and quantitative forms of validation. This paper traces our progress toward developing and operationalizing five common perspectives on teaching adults with a new instrument called the Teaching Perspectives Inventory (TPI)